Mismatched outcomes for biodiversity and ecosystem services: testing the responses of crop pollinators and wild bee biodiversity to habitat enhancement. (4th December 2019) - Nicholson, Charlie C.; Ward, Kimiora L.; Williams, Neal M.; Isaacs, Rufus; Mason, Keith S.; Wilson, Julianna K.; Brokaw, Julia; Gut, Larry J.; Rothwell, Nikki L.; Wood, Thomas J.; Rao, Sujaya; Hoffman, George D.; et al.
Abstract: Supporting ecosystem services and conserving biodiversity may be compatible goals, but there is concern that service‐focused interventions mostly benefit a few common species. We use a spatially replicated, multiyear experiment in four agricultural settings to test if enhancing habitat adjacent to crops increases wild bee diversity and abundance on and off crops. We found that enhanced field edges harbored more taxonomically and functionally abundant, diverse, and compositionally different bee communities compared to control edges. Enhancements did not increase the abundance or diversity of bees visiting crops, indicating that the supply of pollination services was unchanged following enhancement. We find that actions to promote crop pollination improve multiple dimensions of biodiversity, underscoring their conservation value, but these benefits may not be spilling over to crops. More work is needed to identify the conditions that promote effective co‐management of biodiversity and ecosystem services. Abstract : We found that enhanced field edges harbored more taxonomically and functionally abundant, diverse, and different bee communities compared to control edges. Enhancements did not increase the abundance or diversity of bees visiting crops, indicating that the provision of pollination services was unchanged following enhancement. We find that actions to promote crop pollination improve multiple dimensions of biodiversity, underscoring their conservation value, but these benefits may not be spilling over to crops.